Preparation and Reactivity of 3-Amino-2,4-dichloroquinoline - Šimáček, Adam; Grepl, Martin; Hradilová, Ludmila; Hradil, Pavel (Synlett, 2012)
A simple and efficient synthesis of 2-substituted 3-amino-4-chloroquinolines and 2,4-disubstituted 3-aminoquinolines was carried out by reacting 3-amino-2,4-dichloroquinoline with various oxygen-, sulfur- and nitrogen-containing nucleophiles.
Keywords: heterocycles; quinolones; dichloroquinoline; aminoquinoline; substitution